Influence of Graphene Nanosheets on Rheology, Microstructure, Strength Development and Self-Sensing Properties of Cement Based Composites - Ur Rehman, Sardar Kashif; Ibrahim, Zainah; Memon, Shazim; Aunkor, Md Toasin Hossain; Faisal Javed, Muhammad; Mehmood, Kashif; Shah, Syed (MDPI, 2018)
In this research, Graphene oxide (GO), prepared by modified hammer method, is characterized using X-ray Diffraction (XRD), Fourier Transform Infrared (FT-IR) Spectrometry and Raman spectra. The dispersion efficiency of GO in aqueous solution is examined by Ultraviolet-visible spectroscopy and it is found that GO sheets are well dispersed. Thereafter, rheological properties, flow diameter, hardened density, compressive strength and electrical properties of GO based cement composite are investigated by incorporating 0.03% GO in cement matrix. The reasons for improvement in strength are also discussed. Rheological results confirm that GO influenced the flow behavior and enhanced the viscosity of the cement based system. From XRD and Thermogravimetric Analysis (TGA) results, it is found that more hydration occurred when GO was incorporated in cement based composite. The GO based cement composite improves the compressive strength and density of mortar by 27% and 1.43%, respectively. Electrical properties results showed that GO-cement based composite possesses self-sensing characteristics. Hence, GO is a potential nano-reinforcement candidate and can be used as self-sensing sustainable construction material.